(untitled) (CIPEEX, 2022)
RHEUMATOID ARTHRITIS IS A CHRONIC AND PROGRESSIVE DISEASE THAT AFFECTS ABOUT 1% OF THE BRAZILIAN POPULATION. THIS STUDY AIMED TO DESCRIBE THE SOCIODEMOGRAPHIC AND CLINICAL ANALYSIS OF PATIENTS WITH RHEUMATOID ARTHRITIS TREATED AT THE RHEUMATOLOGY SERVICE OF THE GENERAL HOSPITAL OF GOINIA DURING THE PERIOD FROM 2016 TO 2021. THIS IS A CROSS-SECTIONAL, RETROSPECTIVE AND QUANTITATIVE STUDY. THE SAMPLE CONSISTED OF 209 PATIENTS, AND DATA WERE COLLECTED THROUGH RESEARCH IN ELECTRONIC MEDICAL RECORDS BASED ON A COLLECTION FORM ELABORATED BY THE RESEARCHERS. IT WAS OBSERVED THAT MOST PATIENTS WERE FEMALE (85.2%), AGED 60 YEARS OR OLDER (54.5%) AND SINGLE (66%). REGARDING CLINICAL DATA, 89.5% OF THE PATIENTS HAD SOME COMORBIDITY, WITH SYSTEMIC ARTERIAL HYPERTENSION BEING THE MOST PREVALENT, 89% USED ANOTHER CONTINUOUS MEDICATION FOR THE TREATMENT OF COMORBIDITIES AND THE MOST USED WAS VITAMIN D. IN ADDITION, 80.4% USED SYNTHETIC DISEASE-MODIFYING MEDICATIONS AND THE MOST USED WAS METHOTREXATE (50.7%). AMONG THOSE WHO USED SPECIFIC TARGET BIOLOGICAL OR SYNTHETIC DRUGS, THE MOST USED WAS ADALIMUMAB (6.7%). 60.8% OF THE PATIENTS USED CORTICOSTEROIDS (PREDNISONE). THE MOST COMMONLY USED THERAPEUTIC REGIMEN WAS METHOTREXATE ASSOCIATED CORTICOSTEROIDS (23.9%). IT IS CONCLUDED, THEREFORE, THAT IN A MORE DETAILED ANALYSIS OF THE PROFILE AND DRUG TREATMENT INSTITUTED IN PATIENTS, MOST OF THE DATA FOUND WERE SIMILAR TO THOSE FOUND IN THE SCIENTIFIC LITERATURE AND MOST OF THE SCHEMES USED AGREE WITH THE CLINICAL PROTOCOL OF THERAPEUTIC GUIDELINES (2021) OF THE MINISTRY OF HEALTH FOR RHEUMATOID ARTHRITIS.